SCIENTIFIC AND TECHNICAL SOLUTIONS TO INCREASE THE LIFE OF PNEUMATIC TIRES OF THE UNIT FOR PROCESSING BETWEEN THE COTTON ROWS (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article covers the issues of increasing the efficiency of pneumatic tires installed on agregate wheels during row-spacing of cotton processing in agricultural cotton growing, factors affecting the performance of tire life, fuel consumption, as well as reducing tread wear.